2006
DOI: 10.1021/jp0648285
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Mesoporous Ceria with Hierarchical Nanoarchitecture Controlled by Amino Acids

Abstract: In this work, we report the synthesis and characterization of mesoporous ceria with hierarchical nanoarchitectures controlled by amino acids. During the synthesis procedure, cerium oxalate precipitate was treated hydrothermally with different amino acids as crystallization modifiers, and hierarchically structured cerium oxalate precursors were obtained. Ceria can be produced after thermal decomposition of the cerium oxalate precursors. Structure and properties of the product were characterized by X-ray diffrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(71 citation statements)
references
References 54 publications
5
65
0
1
Order By: Relevance
“…The deconvoluted binding energies of Ce 3d spectra are summarized in Table 2, which distinctly shows that the fraction of Ce 3+ (intensities of υ 1 and u 1 ) significantly decreased on account of the formation of CeO 2 for the 80% NiO-CeO 2 /AAO. It is obvious that the observed binding energies of Ce 4+ and Ce 3+ are consistent with the previous reports [35,36]. The appearance of characteristic Ce 3+ bands are labelled at 884.4 eV (υ 1 ) and 900.8 eV (u 0 ) suggests that Ce existed in both Ce 3+ and Ce 4+ oxidation states on the surfaces of the 20%, 50% and 80% NiO-CeO 2 /AAO.…”
Section: Characterization Of the Catalyst Before Reactionsupporting
confidence: 90%
“…The deconvoluted binding energies of Ce 3d spectra are summarized in Table 2, which distinctly shows that the fraction of Ce 3+ (intensities of υ 1 and u 1 ) significantly decreased on account of the formation of CeO 2 for the 80% NiO-CeO 2 /AAO. It is obvious that the observed binding energies of Ce 4+ and Ce 3+ are consistent with the previous reports [35,36]. The appearance of characteristic Ce 3+ bands are labelled at 884.4 eV (υ 1 ) and 900.8 eV (u 0 ) suggests that Ce existed in both Ce 3+ and Ce 4+ oxidation states on the surfaces of the 20%, 50% and 80% NiO-CeO 2 /AAO.…”
Section: Characterization Of the Catalyst Before Reactionsupporting
confidence: 90%
“…The 3d 5/2 corresponded to v, while the 3d 3/2 corresponded to u. The doublets (v, u), (v", u"), and (v , u ) represent the 3d 10 4f 0 initial electronic state assigned to Ce 4+ , whereas the signals (v , u ) and (v 0 , u 0 ) represent the 3d 10 4f 1 state of Ce 3+ [12,38,39]. Furthermore, the relative abundance of the Ce 3+ /Ce 4+ of each sample was estimated by considering the area of the deconvolution peaks.…”
Section: Xps Studiesmentioning
confidence: 99%
“…Here, three kinds of surface oxygen species were identified. The peak with binding energy at 531.1-531.3 eV can be attributed to the defect oxide or the surface oxygen ions with low coordination and weakly-bonded oxygen species (O ads ) adsorbed on oxygen vacancies, and the peak with binding energy at 532.3-532.7 eV is assigned to adsorbed oxygen species from hydroxyl and adsorbed water species (O w ) on the surface [38,40]. The peak with binding energy at 529.1-529.5 eV was ascribed to lattice oxygen (O latt ) [23].…”
Section: Xps Studiesmentioning
confidence: 99%
“…Lykhach [13,14] also found that CeO 2 activation led to the rapid formation of carbonate and surface carboxylates. Meanwhile, various 1D and 2D CeO 2 nanostructures, [15][16][17] including nanorods, [18] nanowires, [19] nanotubes, [20,21] nanobelts [22,23] and other morphologies [24][25][26][27][28] had been synthesized via the thermal decomposition of CeCO 3 OH precursors, which was often prepared by solution precipitation, [29] sol-gel, [30] microemulsion, [31] sonochemical, [32] hydrothermal methods. [33] However, these synthetic processes usually were complicated with high synthesis cost due to the expensive templates and additives.…”
Section: Introductionmentioning
confidence: 99%